De la hermenéutica a la acción comunicativa. Entre la experiencia de la nada y la experiencia del tú - Arce Carrascoso, José Luis; Ferranons Sánchez, Jaume (Logos. Anales del Seminario de Metafísica, 2002)
The starting point of this study is the concept of the “world-opening instance” one of the most carefully created concepts in philosophical reflection, from the predominance of the being, via consciousness, to a singular mode of experience which finds its support in finiteness and dispossession . The main points of the article are the analysis of the fragile itinerary of subjectivity, the study of Da-seinas the limit of the substantialist ontology, and the experience of negativity as an appropriate form for illuminating the manifestation of the self. The article highlights the contrast between this and the experience of the “you”, proposed by Gadamer and by Habermas theory of communicative action.